Simplify 12−4÷43+1

1 answer

12 - 4 ÷ 43 + 1 can be simplified using the order of operations (PEMDAS/BODMAS).

First, we divide 4 ÷ 43: 4 ÷ 43 = 0.093

Then, we substitute this value back into the expression:

12 - 0.093 + 1

Next, we subtract 0.093 from 12: 12 - 0.093 = 11.907

Finally, we add 11.907 to 1: 11.907 + 1 = 12.907

So, the simplified answer is 12.907.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions